COMMUNICATIVE PARADIGM IN REFLECTIONS OF THE EDUCATIONAL PROCESS - Ayta Sakun ("Scientific Information Agency "Science-technologies-information" LLC, 2019)
The dominant feature of today is the "knowledge society" - a worldview and scientific concept, updated by social, cultural and philosophical discourses in the process of a thorough rethinking of the theory of "information society". Gaining increasing popularity in connection with the problematization of the cognitive dimensions of education, economics and technology, this concept gains a modern definition: it is a society whose development is based on internal polyphony and the individual abilities of each of its representatives. Thus, in modern society, not only "information", but also "knowledge" plays a special role. The separation and differentiation of these two concepts are of fundamental importance. The modern era (having reached the definition of the "era of knowledge") brings a new understanding of "knowledge."